INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Restukumala, Faisal Yoga (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to provide empirical evidence about the effect of dividend policies and institutional ownerships on firm value. Research is conducted using a quantitative method. This study uses a 5-years period of 2010-2014 to test the hypothesis, while secondary data are employed as research data. To select the samples, a purposive sampling method is conducted which 11 companies in the consumer goods industry are selected. The hypothesis testing is conducted using a multiple linear regression analysis. The results of this study indicate that the dividend policies negatively affect firm value and institutional ownerships positively affect firm value. The negative effect of the dividend policies may reduce companies cash flows which causes them to be unable to meet obligations and are reluctant to pay dividends. Institutional ownership has a positive effect as it is able to monitor managers’ performances.Keywords: dividend policy, institutional ownership, firm value